Official Development Assistance and Demography: South and Central Asia Case - Aleksandra. RABCZUN; Zakaria. TALOUNI (Communications of International Proceedings, 2021)
It is widely known that development shapes population trends. When income is rising, a depletion in the birth rate can be experienced (Brückner, Schwandt, 2013; Sinding, 2009). But the contrary can be also true: population trends can hamper or boost development. While, in the present time, researchers are focusing on examining the relationship between demographic trends, poverty, and economic growth, closer attention should be given to additional factors. Some countries are lacking the internal potentials for growth. They need extraordinary impulse. Since the XXth century, such a role is fulfilled by the official development assistance (ODA). The aforesaid reflects in the form of a commitment by which developed countries are supporting the least developed ones. For many Asian countries, flows from ODA are crucial for investing in economic and social infrastructure. Unfortunately, such development is hampered by a demographic aspect – it is easier to spot progress when indicators are counted only for fewer people. Based on the foregoing, it is compelling to examine the correlation between population and the official development assistance trends. The main aim of this article is to investigate the relation between recipients of the British official development assistance (as one of the biggest donors of ODA worldwide) in Asia and its population. The article thesis is the following: the absorption of funds from the British official development assistance is correlated to the population. It is possible to group Asian countries, depending on the population and received funds, into separate categories.
Keywords: Official Development Assistance; Population; Asia; Demographic Explosion.